Penemuan Hukum dalam Peraturan Badan Narkotika Nasional Tentang Asesmen Terpadu Bagi Pecandu Korban Penyalahgunaan Narkotika - Raihani, Siti Rifqa; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Drug abuse is a complex problem that has wide-ranging impacts on individuals, society, and the state. Within the Indonesian legal system, drug abusers are not always regarded solely as perpetrators of criminal acts, but also as victims who require medical and social treatment. Based on Law Number 35 of 2009 on Narcotics, particularly Article 54, narcotics addicts and victims of drug abuse are required to undergo medical rehabilitation and social rehabilitation. However, the implementation of this provision in judicial practice often gives rise to problems due to differing legal interpretations regarding the status of drug abusers as suspects or defendants. This study aims to analyze legal discovery (rechtvinding) in the process of granting rehabilitation to drug abusers, as well as to identify the role of law enforcement officials—particularly investigators, public prosecutors, and judges—in determining appropriate forms of treatment. The research method employed is normative juridical, using statutory, conceptual, and case approaches. Data were obtained from library research, statutory regulations, court decisions, and literature related to narcotics law enforcement. The results of the study indicate that legal discovery in the granting of rehabilitation is necessary to bridge normative gaps and address inaccuracies in the application of law in drug abuse cases. Legal discovery by judges and law enforcement officials is essential to ensure that the objectives of law—justice, utility, and legal certainty—are achieved in a balanced manner. Rehabilitation is not merely a form of leniency, but a manifestation of human rights protection for drug abusers to obtain treatment and recovery.